Custos ocultos estruturais: um estudo na Secretaria de Saúde do município paraibano de Sapé - Santos, Rodolfo Martins dos (2022)
This research was carried out with the objective of identifying the perception of the employees of a health department about the activities related to the hidden structural costs that occur in the public sector. In this sense, a case study was carried out, having as a sample the servers that work in the Health Department of the municipality of Sapé in Paraíba. For this, the study was operationalized through a survey, which initially were raised based on the literature, which structural hidden costs are likely to occur in the public sector. In a second moment, activities that take place in the basic health units of the aforementioned Secretariat were raised, which are related to hidden structural costs that occur in the public sector. Then questionnaires were applied, in order to understand the perception of the servers about the activities related to the hidden structural costs, and the Likert scale was used. To analyze the responses, the frequency and percentage of occurrence of each response were calculated, as well as the calculation of the Spearman coefficient, in order to analyze the intensity of the relationship between the variables. It was found that of the hidden structural costs that can occur in the public sector, the cost of Rework was the most negatively perceived by the respondents, where their activities were mostly evaluated as Bad or Weak. Thus leading to the understanding that these activities may impair the quality of services offered by the health department. Regarding the relationships between personal data, professional experience and nature of the respondents' relationship and their perceptions about the sources of structural hidden costs, a strong predominant relationship was seen between the professional experience of the servers and the costs of Logistics, Technology and Rework. Possibly evidencing that the longer the server's experience, consequently, he will have a greater understanding and understanding of activities related to logistics, technology and rework costs. Above all, this work contributes to the literature in the area of costs, since there are few works on hidden costs, being even scarcer specifically on hidden costs in the public sector. It can also contribute to the performance of public managers, since such costs can go unnoticed, and managers do not realize how much structural hidden costs can impact the quality of public services offered to the population.